Natural genetic variation of the cardiac transcriptome in non-diseased donors and patients with dilated cardiomyopathy - Heinig, Matthias; Meder, Benjamin; Katus, Hugo (Genome biology, 2017)
Genetic variation is an important determinant of RNA transcription and splicing, which in turn contributes to variation in human traits, including cardiovascular diseases.